PENGUATAN PARIWISATA BERBASIS MASYARAKAT DI DESA WISATA BATU KUMBUNG NUSA TENGGARA BARAT - Fatrisia Yulianie; I Gusti Agung Ayu Widiastri; I Komang Gede Aditya Aristana; Putu Reggina Pritiya Rajani Kaniaka; I Made Sandi Koriada; Dwi Erza Purnama (JURNAL SEWAKA BHAKTI, 2026)
The development of tourism village requires community readiness to ensure that cultural, natural, and creative economic resources can be managed sustainably. This program was conducted to strengthen community insight of Community-Based Tourism (CBT) and improve hospitality competencies rooted in local culture in Batu Kumbung Tourism Village, West Lombok Regency, West Nusa Tenggara. The program was conducted on 21-23 May 2026 through participatory training ang mentoring involving village officials, tourism awareness groups, local entrepreneurs, and community members. The methods included lectures, discussions, service simulations, observations, and participant evaluations. The results indicated increased understanding of community roles in tourism village management, improved awareness of hospitality principles, and stronger commitment to collaborative destination development. Participants also identified future needs for training in tour guiding, tourism  communication, destination promotion, and tourism village management. The activity contributed to improving community readiness in development a sustainable tourism village based on local culture.